Diagnosis of pulmonary hypertension. Issue 1 (24th January 2019) - Frost, Adaani; Badesch, David; Gibbs, J. Simon R.; Gopalan, Deepa; Khanna, Dinesh; Manes, Alessandra; Oudiz, Ronald; Satoh, Toru; Torres, Fernando; Torbicki, Adam
A revised diagnostic algorithm provides guidelines for the diagnosis of patients with suspected pulmonary hypertension, both prior to and following referral to expert centres, and includes recommendations for expedited referral of high-risk or complicated patients and patients with confounding comorbidities. New recommendations for screening high-risk groups are given, and current diagnostic tools and emerging diagnostic technologies are reviewed. State of the art and research perspectives in the diagnostic procedures of patients with pulmonary hypertension including a comprehensive diagnostic algorithm http://ow.ly/Ow9730mknM6